PERÃODOS DE PROTEÃ‡ÃƒO DO FEIJOEIRO AO ATAQUE DE ð˜‰ð˜¦ð˜®ð˜ªð˜´ð˜ªð˜¢ ð˜µð˜¢ð˜£ð˜¢ð˜¤ð˜ª BIÃ“TIPO B, NA Ã‰POCA DE SEMEADURA DO INVERNO - Pereira, Marcelo F. A.; BoiÃ§a Jr., Arlindo L. (REVISTA DE AGRICULTURA, 2020)
PERÃODOS DE PROTEÃ‡ÃƒO DO FEIJOEIRO AO ATAQUE DE ð˜‰ð˜¦ð˜®ð˜ªð˜´ð˜ªð˜¢ ð˜µð˜¢ð˜£ð˜¢ð˜¤ð˜ª BIÃ“TIPO B, NA Ã‰POCA DE SEMEADURA DO INVERNO